A 10 year single centre experience of percutaneous and endoscopic extraction of bile duct stones with T tube in situ. Issue 9 (September 1991) - Nussinson, E; Cairns, S R; Vaira, D; Dowsett, J F; Mason, R R
Abstract : A non-randomised single centre study of 226 consecutive patients referred over 10 years with retained common bile duct stones and a T tube in situ or a cholecystostomy tube are reported. Percutaneous extraction was attempted in 204 and endoscopic extraction in 68 patients. Percutaneous clearance was achieved in 158 (77.5%) patients and endoscopic clearance in 52 (76.5%) patients. Six of 153 (3.9%) patients followed after percutaneous treatment suffered major complications (pancreatitis, cholangitis, or tract perforation). Three of 67 (44%) patients followed after endoscopic treatment suffered major complications (pancreatitis, cholangitis, or bleeding). When the initial method of treatment failed, the alternative was used, resulting in an overall success rate of bile duct clearance of 94.3%. It is concluded that percutaneous and endoscopic methods of bile duct clearance in patients with a T tube in situ are equally effective, carrying similar complication rates. This study has helped to clarify the indications and efficacy of these alternative treatments.